Modulation of TNF-induced macrophage polarization by synovial fibroblasts - Donlin, Laura T. (2014)
Mesenchymal stromal cells have emerged as powerful modulators of the immune system. Here we explored how the human macrophage response to tumor necrosis factor (TNF) is regulated by human synovial fibroblasts, the representative stromal cell type in the synovial lining of joints that become activated during inflammatory arthritis. We found that synovial fibroblasts strongly suppressed TNF-mediated induction of an interferon (IFN)-β autocrine loop and downstream expression of IFN-stimulated genes (ISGs), including chemokines CXCL9 and CXCL10 that are characteristic of classical macrophage activation. TNF induced the production of soluble synovial fibroblast factors that suppressed the macrophage production of IFN-β, and cooperated with TNF to limit the responsiveness of macrophages to IFN-β by suppressing activation of Jak-STAT signalling. Genome-wide transcriptome analysis showed that co-cultured synovial fibroblasts modulate the expression of approximately one third of TNF-regulated genes in macrophages, including genes in pathways important for macrophage survival and polarization towards an alternatively activated phenotype. Pathway analysis revealed that gene expression programs regulated by synovial fibroblasts in our co-culture system were also regulated in rheumatoid arthritis (RA) synovial macrophages, suggesting that these fibroblast-mediated changes may contribute to RA pathogenesis. This work furthers our understanding of the interplay between innate immune and stromal cells during an inflammatory response, one that is particularly relevant to inflammatory arthritis. Our findings also identify modulation of macrophage phenotype as a new function for synovial fibroblasts that may prove to be a contributing factor in arthritis pathogenesis.